2022
DOI: 10.3390/horticulturae8070592
|View full text |Cite
|
Sign up to set email alerts
|

Shading Inhibits Sugar Accumulation in Leaf and Fruit of Jujube (Ziziphus jujuba Mill.)

Abstract: Jujube is a characteristic light-demanding fruit tree, but fruit quality is frequently degraded because of the weak light in protected cultivation facilities in south China. In this study, a black shade net was used to set three light intensities artificially: no shading (0%, control, NS), moderate shading (45%, MS), and severe shading (76%, SS) to investigate the effect of low light on sugar metabolism of jujube. Compared with NS, chlorophyll and carotenoid contents in shaded leaves were increased, while spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
2
0
1
Order By: Relevance
“…It is clear from the above that there are various factors affecting the growth and development of jujube trees and fruits. This is consistent with previous studies [ 37 , 38 ]. It is of great importance for the development of the jujube industry to comprehensively analyze the key meteorological factors and soil nutrients that affect the productivity and fruit quality, and screen out the improved cultivars that can adapt to specific environmental conditions.…”
Section: Discussionsupporting
confidence: 94%
“…It is clear from the above that there are various factors affecting the growth and development of jujube trees and fruits. This is consistent with previous studies [ 37 , 38 ]. It is of great importance for the development of the jujube industry to comprehensively analyze the key meteorological factors and soil nutrients that affect the productivity and fruit quality, and screen out the improved cultivars that can adapt to specific environmental conditions.…”
Section: Discussionsupporting
confidence: 94%
“…Low-light stress reduces the photosynthetic performances of the plants, and the transportation of photosynthetic products from leaves to fruits are also affected [ 6 , 9 ], which ultimately leads to the reduction in the sugar content in fruits. Similar research results have been reported on melon [ 16 ], strawberry [ 6 ] and jujube [ 17 ]. Nitrogen metabolism was disturbed by shading, which induced the decrease in dry matter accumulation, ultimately resulting in the failure of watermelon fruits to expand normally [ 18 ].…”
Section: Resultssupporting
confidence: 89%
“…[37] on tomato has shown that the soluble sugar content is higher in plants grown in the shade compared with those grown in full sun. These results are at odds with those of Wang et al [38] on Ziziphus jujuba Mill and [39] on grapevine (Vitis vinifera). According to them, sugar content reduction is obtained in plants grown in the shade compared with those grown in full sun.…”
Section: Shading and Plant Materials Effect On Physiological And Bioc...contrasting
confidence: 58%